Exploring the binding sites of VRT534 at Cx26 as a putative chemical chaperone for targeted treatment of hereditary hearing disorders - Harre, Jennifer; Wang, Dahua; Warnecke, Athanasia; Zeilinger, Carsten (Frontiers in Medicine, 2025)
Hearing loss is the most common sensory disorder, significantly affecting the quality of life for millions of people worldwide. Chemical chaperones are emerging as a potential therapeutic option for hereditary forms of deafness associated with protein misfolding. VRT534, a chemical chaperone previously used in the treatment of cystic fibrosis, has been shown to modulate the activity of mutated forms of human connexin 26 (Cx26), a gap junction protein crucial for auditory function. However, the precise molecular mechanism of its interaction with Cx26 remains unclear. In this study, we investigated the ability of VRT534 to bind and functionally rescue mutant Cx26. Structural models of Cx26 were generated using AlphaFold3 and analyzed via Diff-Dock-L for binding prediction. Functional restoration by VRT534 was tested using an automated patch-clamp in HeLa cells expressing wild-type or mutant Cx26 (Cx26WT, Cx26L90P, Cx26F161S, and Cx26R184P). VRT534 restored channel function in Cx26L90P and Cx26R184P, but not in Cx26F161S. Docking data revealed stronger binding affinity of VRT534 to mutant variants, with putative binding sites located near the pore region. These findings provide new insight into the selective rescue of mutant Cx26 and support further development of chemical chaperones for hereditary hearing loss.